2019
DOI: 10.3389/fphys.2019.01512
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Computational Modeling-Guided Persistent Atrial Fibrillation Ablation: Updated Outcome of Multicenter Randomized Study

Abstract: Objective: Catheter ablation of persistent atrial fibrillation (AF) is still challenging, no optimal extra-pulmonary vein lesion set is known. We previously reported the clinical feasibility of computational modeling-guided AF catheter ablation. Methods: We randomly assigned 118 patients with persistent AF (77.8% men, age 60.8 ± 9.9 years) to the computational modeling-guided ablation group (53 patients) and the empirical ablation group (55 patients) based on the operators' experience. For virtual ablation, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…With the development of high-speed parallel computing hardware system (Boyle et al, 2019 ), AF simulation modeling has become more efficient for clinical applications. In particular, we previously reported that AF catheter ablation results can be predicted and improved by using computational modeling before the procedure (Kim et al, 2019 ). In this study, we created the realistic atrial model by reflecting personalized electroanatomy and modulating the specific ion currents for AADs.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-speed parallel computing hardware system (Boyle et al, 2019 ), AF simulation modeling has become more efficient for clinical applications. In particular, we previously reported that AF catheter ablation results can be predicted and improved by using computational modeling before the procedure (Kim et al, 2019 ). In this study, we created the realistic atrial model by reflecting personalized electroanatomy and modulating the specific ion currents for AADs.…”
Section: Introductionmentioning
confidence: 99%
“…The CUVIA-AF 1 trial was the only prospective RCT of computational modeling-guided AFCA published to date ( 10 , 11 ). Kim et al ( 10 ) conducted a preprocedural virtual ablation to test the optimal linear lesion set using AF modeling (CUVIA version 1.0) ( 32 ), which reflected the patient-specific atrial anatomy, and adopted the best lesion set during the clinical AFCA procedure, which was superior to the empirical ablation in patients with PeAF.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the use of the current sequential atrial substrate mapping technology with a multielectrode catheter is not adequate to find the AF driver, as in contrast to the remarkable improvements made in the catheter technology for a long-lasting PV isolation (PVI). Recently, computational modeling has demonstrated the potential applicability in cardiac arrhythmia interventions ( 10 , 11 ). Computational modeling allows for high-density, entire-chamber mapping while reflecting the personalized atrial anatomy and physiology ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations